Changes in β2-Glycoprotein I Antigenicity Induced by Phospholipid Binding - Wagenknecht, Dawn R; McIntyre, John A (Thrombosis and Haemostasis, 1993)
β2-glycoprotein I (β2GPI) or apolipoprotein H has been described as a necessary cofactor for antiphospholipid antibody (aPA) binding in ELISA. Some investigators disagree with the β2-GPI requirement whereas data from other laboratories indicate that β2GPI, not phospholipid (PL), is the antigen for aPA. To investigate the cofactor we have produced three IgG1 monoclonal antibodies (mAb) to human β2GPI; 3G9, 1B4 and 3D11. Western blot analyses showed the mAb to bind human β2GPI (40 kDa), but no reactivity was observed with adult or fetal bovine sera. In contrast, rabbit anti-β2GPI reacted with both human and bovine sera. None of the mAb reacted with phosphatidylserine (PS) or cardiolipin (CL) by ELISA. There were no significant differences in ELISA binding to purified β2GPI when the mAb were adjusted to the same concentration. mAb 3G9 and 1B4 gave stronger signals in ELISA after β2GPI bound to PS; the increase for 3G9 was significantly greater than for 1B4 (p <0.002). mAb 3D 11 was unique inasmuch as it failed to recognize β2PGI bound to PS. In comparison, the rabbit anti-β2GPI was unaffected by PS-β2GPI binding. These observations indicate that the mAb recognize three distinct epitopes on β2GPI. The data suggest that β2GPI undergoes conformational changes subsequent to binding PL. Our findings are consistent with the hypothesis that aPA recognize a β2GPI neotope formed subsequent to binding PL.